The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/cid.12882
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic evaluation of single implant restorations, adjacent single implant restorations, and implant‐supported fixed partial dentures: A 1‐year prospective study

Abstract: Background Peri‐implant soft tissues esthetics varies and depends on the restoration type such as implant‐supported single crowns, adjacent multiple single crowns, and fixed partial dentures (FPD). Purpose The aim of this prospective study was to assess the esthetic outcome of the peri‐implant soft tissues of (NobelBiocare™) implant‐supported single crowns, adjacent multiple single crowns, and FPD. A potential association between the esthetic risk profile and the esthetic outcome was assessed. Materials and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In our study, participants responded similarly that loss of the interdental papilla, gingival recession, exposure of the implant margin and a poor emergence profile are the most common aesthetic complications associated with dental implants. Recent studies in the literature have reported aesthetic complications, revealing that between 4 and 16% of single implant crowns in the anterior maxilla fail for aesthetic reasons [48][49][50]. The most common aesthetic complication is gingival recession exposing the implant/abutment junction, with one study reporting up to 61% of cases with at least 1 mm of gingival recession on the facial aspect.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, participants responded similarly that loss of the interdental papilla, gingival recession, exposure of the implant margin and a poor emergence profile are the most common aesthetic complications associated with dental implants. Recent studies in the literature have reported aesthetic complications, revealing that between 4 and 16% of single implant crowns in the anterior maxilla fail for aesthetic reasons [48][49][50]. The most common aesthetic complication is gingival recession exposing the implant/abutment junction, with one study reporting up to 61% of cases with at least 1 mm of gingival recession on the facial aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Full‐text assessment was performed for 327 articles. Based on the predetermined inclusion criteria, 121 articles were included 14–20,22,23,30–141 . The reason for exclusion of the other 196 articles is available in the Appendix (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The pink esthetic score (PES) 16 was utilized in 58 studies (62.4% of the studies assessing PMC with an index), 16,17,33–35,46,49–54,56–66,69–71,74,76,79,81,83,84,94,96–100,105,107–112,114–116,118–122,124,127,128,133,134 while the combined pink and white esthetic score (PES/WES) 142 was employed in 26 articles (28.0%) 17,31,37,38,41–45,47,55,72,73,80,90–92,102,103,106,117,135,136,139–141 . Other esthetic indices utilized include the Copenhagen index score (CIS), 85–88 the implant crown esthetic index (ICAI), 17,75 the complex esthetic index (CEI), 17,32,95 the implant esthetic score (IAS), 17 the implant restoration esthetic index (IREI), 100 the mucosal scarring index (MSI) 54,143 and the implant soft tissue dehiscence coverage esthetic score (IDES) 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implant system is designed with a tapered body and variable threads (deeper at the apical area) to increase self‐drilling ability and primary stability through condensing peri‐implant bone tissue during the insertion. Most studies exhibited the acceptable outcome of this implant system based on short‐term follow‐up (Babbush et al, 2013; Boon et al, 2020), and the implant survival rates could reach over 95% (Blume et al, 2020; Kielbassa et al, 2009; Kolinski et al, 2014). However, the sample size was relatively small in these studies (66–199 implants) and some literature revealed that the efficacy of the VTTI system after functional loading was not clear (Blume et al, 2020; Cristalli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%